Medical Applications of Virtual Environments - Riva, G. (Yearbook of Medical Informatics, 2003)
Technologies that were hardly used ten years ago, such as the Internet, e-mail, and video teleconferencing are becoming familiar methods for diagnosis, therapy, education and training. However, the possible impact of virtual reality (VR) on health care is even higher than the one offered by the new communication technologies. In fact, VR is a technology, a communication interface and an experience: a communication interface based on interactive 3D visualization, able to collect and integrate in single real-like experience different inputs and data sets.The first health care applications of VR started in the early ‘90s with the need for medical staff to visualize complex medical data, particularly during surgery and for surgery planning. A couple of years later, the scope of VR applications in medicine has broadened to include neuropsychological assessment and rehabilitation.This paper intends to investigate the role of VR in medicine, presenting some of the most interesting applications actually developed in the area. Moreover, it discusses the clinical principles, technological devices and safety issues associated with the use of virtual reality in medicine.